Understanding the impact of chemotherapy on the immune landscape of high-grade serous ovarian cancer - Rami Vanguri; Jamal Benhamida; Jonathan H. Young; Yanyun Li; Oliver Zivanovic; Dennis Chi; Alexandra Snyder; Travis J. Hollmann; Katherine L. Mager (Elsevier, 2022)
Objectives: We quantitatively characterized the change in temporospatial expression of repressive and stimulatory checkpoints across immune cell populations in the tumor microenvironment in a cohort of high grade serous ovarian carcinomas (HGSOC) using matched samples before and after neoadjuvant platinum-based chemotherapy. Methods: Using retrospectively collected matched tissue samples from 9 patients, cell populations were assessed using multiplex immunofluorescence using the Vectra Multispectral Imaging System (Perkin Elmer). We used multiple panels to assess: tumor (AE1/AE3), T cells (CD3, CD8, FOXP3), macrophages (CD68) as well as immune checkpoints (C3aR, PD-1, PD-L1, LAG3, IDO, ICOS, GITR). IHC staining was performed for folate receptor status. Changes in immune cell populations as well as intensities of associated repressive and stimulatory proteins were assessed pre- to post-treatment. Results: We observed a consistently high pre-treatment stromal macrophage population which is reduced post-chemotherapy with post-treatment enrichment in macrophage PD-L1 expression. While inhibitory checkpoint expression on T cells was heterogeneous post-chemotherapy, we observed a change in the ThICOS+:Treg ratio which resulted in ThICOS+ cells outnumbering Treg cells post-treatment. Spatial analysis revealed the proximity of Treg cells to ThICOS+ T cells decreased post-treatment. We also observed upward shifts in Teff:Treg T cell ratios with retention of immune checkpoints PD-1, LAG3 and GITR. Conclusions: In this unique dataset of pre and post matched chemotherapy treated HGSOC patients, we observed changes in immune cell subsets expressing repressive or stimulatory proteins resulting in immune compositions more favorable to checkpoint modulations, suggesting novel therapeutic strategies in the recurrent setting.